Introduction - Mhd. Sarif, Suhaimi; Ismail, Yusof (Kulliyyah of Economics and Management Sciences IIUM, 2021)
This chapter provides an introduction to the topic of contemporary theory of social entrepreneurship. This chapter argues that social entrepreneurship is not a new discipline in the studies of economics and entrepreneurship. It evolves from the study of the firm. The emergence of social entrepreneurship is parallel with the development of business entrepreneurship with an attention to social concerns.